Ένταξη Θεατρικών Τεχνικών σε Μαθησιακό Πλαίσιο: Αυθεντική Αξιολόγηση Μαθησιακών Στόχων - Παπαδόπουλος Σίμος (Education Sciences, 2015)
When the drama conventions are integrated with the learning context, they can transform the dramatic context into teaching-learning one. The dramatic activities are organized basically upon the learning objectives, creating an excellent environment for the authentic assessment’s application. The paper’s aim is to enquire the process of dramatic - pedagogical activities’ assessment in the teaching environment. In the beginning, the article refers to the dramatic conventions and their importance in learning procedure. Then, a complete dramatic- pedagogical model of learning assessment (bodily-scenic expression, communication, cognition, psycho- dynamic creation) is proposed, where the teacher chooses the objectives which are considered to be more appropriate, according to the kind and the context of the dramatic- learning activities. Finally, there is a description of the conventions used for the activities’ assessment (self- assessment, conversation- reflection, rubric and students’ portfolio).